Speech at the Official Launch of the Green Climate Fund Secretariat, Songdo, Korea, December 4, 2013 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, called this an extremely important day. Man-made climate change is real and is having a significant impact-- an increasing impact. We are convinced that there is no way that we will be able to end poverty by 2030, without tackling climate change in the most serious manner. He praised the Green Climate Fund as a source of enormous optimism and hope in the fight against climate change, and said the Fund was an "historic opportunity" to protect future generations.